A simple and efficient method for enrichment of cocoa polyphenols from cocoa bean husks with macroporous resins following a scale-up separation. (February 2019) - Zhong, Jia-Lun; Muhammad, Nadeem; Gu, Yu-Chao; Yan, Wei-Dong
Abstract: The aim of this study is to develop an efficient method for the decaffeination and enrichment of the polyphenols from cocoa husks extracts. LX-17 was selected for the exploration of optimal processing parameters from eight kinds of macroporous resins. The adsorption kinetics and thermodynamics of (−)-epicatechin (EC) were studied prior to the scale-up separation. The optimum parameters for separation were as follow: 6.0 mg/mL cocoa extracts, pH 2.0, 25 °C column temperature, flow rates of adsorption and desorption 1.6 BV/h (Bed Volume, the volume of the resin) and ethanol-water (20:80, 50:50, 95:5, v/v) solutions in the gradient elution. In the scale-up separation, 2 kg of cocoa husks were extracted in 20 L 50% ethanol solutions, separated on 3 L LX-17 resins and yielded 34.99 g cocoa polyphenols. This method significantly increased the total polyphenol contents from 2.23% to 62.87% with a recovery yield of 78.57%. Highlights: Polyphenols from cocoa husks can be enriched with macroporous resins. The content of total polyphenols increased from 1.34% to 57.9%. Adsorption kinetics and thermodynamics are studied respectively. Caffeine and polyphenols were enriched in two fractions using LX-17 resin. The scaling-up separation was found satisfactory.